2019
DOI: 10.1073/pnas.1820320116
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory changes in pterin and carotenoid genes underlie balanced color polymorphisms in the wall lizard

Abstract: Reptiles use pterin and carotenoid pigments to produce yellow, orange, and red colors. These conspicuous colors serve a diversity of signaling functions, but their molecular basis remains unresolved. Here, we show that the genomes of sympatric color morphs of the European common wall lizard (Podarcis muralis), which differ in orange and yellow pigmentation and in their ecology and behavior, are virtually undifferentiated. Genetic differences are restricted to two small regulatory regions near genes associated … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
165
2
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 176 publications
(187 citation statements)
references
References 50 publications
(58 reference statements)
14
165
2
2
Order By: Relevance
“…The possibility that these two species share the same sex chromosome turnover is excluded by the size of the chromosomes which constitute the LST_L probe: they belong to the fraction of small chromosomes, whereas LAG5/LST5 are nearly twice as large. The small size of the Z chromosome in L. agilis and L. strigata fits well with the results of Rovatsos et al [2016, 2019] and Andrade et al [2019], which showed that the lacertid Z originates from two fused microchromosomes of ancestral squamates.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The possibility that these two species share the same sex chromosome turnover is excluded by the size of the chromosomes which constitute the LST_L probe: they belong to the fraction of small chromosomes, whereas LAG5/LST5 are nearly twice as large. The small size of the Z chromosome in L. agilis and L. strigata fits well with the results of Rovatsos et al [2016, 2019] and Andrade et al [2019], which showed that the lacertid Z originates from two fused microchromosomes of ancestral squamates.…”
Section: Discussionsupporting
confidence: 86%
“…The authors suggested that the Z chromosome of lacertids should be one of the small macrochromosomes, formed via fusion of two ancestral squamate microchromosomes [Uno et al, 2012]. Their results were supported by the genome sequencing project of Podarcis muralis [Andrade et al, 2019].…”
Section: Introductionmentioning
confidence: 99%
“…Unlike for the other breeds, we found that urucum canaries were homozygous for a large continuous genomic segment defined by 13 SNPs, spanning a physical interval of 104 kb (770,364-874,443) that harbored eight protein-coding 7 genes: NCAM1, PTS, BCO2, TEX12, IL18, SDHD, LOC103822986, DLAT ( Fig 3B; Table S5). Of these, the BCO2 represents a strong candidate for the gene underlying the urucum phenotype since it encodes an enzyme that is known to cleave carotenoids (19,20) and has been previously implicated in carotenoid pigmentation of the integument in birds and reptiles (21)(22)(23)(24).…”
Section: High-resolution Mapping Of the Urucum Phenotypementioning
confidence: 99%
“…Amplification of the cDNA template with 5' labeled primers was done with the protocol 18 described in (24). Amplicons were sequenced on an Illumina MiSeq system (MiSeq v3 500cycle kit, 2x250 bp reads).…”
Section: Allelic Imbalancementioning
confidence: 99%
“…Colour-polymorphic taxa provide interesting model systems for investigating both the scope and mechanisms of such pleiotropy of master-regulatory loci via gene interactions. Heritable colour morphs typically differ in multiple physiological, developmental and life-history traits (McKinnon and Pierotti 2010), while having a relatively simple genetic basis of one or a few loci with restricted recombination in between them (Joron et al 2006;Lamichhaney et al 2016;Lindtke et al 2017;Andrade et al 2019). The genetic basis and molecular mechanisms behind the phenotypic differences of such heritable colour morphs can therefore reveal direct or indirect interactions between colour-morph loci and other loci influencing suites of phenotypic traits.…”
Section: Introductionmentioning
confidence: 99%